Biologic regulation of physical activity - Rowland, Thomas W. (Champaign, IL Human Kinetics, 2017)
Biologic Regulation of Physical Activity provides readers with a cutting-edge perspective of underlying issues that may contribute to the obesity epidemic. It offers evidence of a biologic regulator affecting physical activity and explores implications of such biologic control on activity.
The nature of physical activity -- Physical activity across the lifespan -- Effect of sex -- Neurochemical models -- Perturbations of brain function -- Organized variability -- Genetic influences -- Physical activity play -- Activity regulation and the need for energy balance -- Mechanisms for biologic control -- Responses to activity interventions -- Understanding obesity: the biologic perspective -- Altering the biologic control of activity.
Includes bibliographical references (pages 171-197) and index.
Keywords: Energy metabolism; Energy Metabolism -- Physiology; Exercise -- Physiological aspects; Brain -- Physiology